ANTIBIOFILM EFFECTS of Citrus limonum and Zingiber officinale Oils on BIOFILM FORMATION of Klebsiella ornithinolytica, Klebsiella oxytoca and Klebsiella terrigena SPECIES - Avcioglu, Nermin Hande; Sahal, Gulcan; Bilkay, Isil Seyis (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Microbial cells growing in biofilms, play a huge role in the spread of antimicrobial resistance. In this study, biofilm formation of Klebsiella strains belonging to 3 different Klebsiella species (K. ornithinolytica, K. oxytoca and K. terrigena), cooccurences’ effect on biofilm formation amount and anti-biofilm effects of Citrus limon and Zingiber officinale essential oils on biofilm formations of highest biofilm forming K. ornithinolytica, K. oxytoca and K. terrigena strains were determined. Materials and Methods: Anti-biofilm effects of Citrus limon and Zingiber officinale essential oils on biofilm formations of highest biofilm forming K. ornithinolytica, K. oxytoca and K. terrigena strains were investigated. Results: 57% of K. ornithinolytica strains and 50% of K. oxytoca strains were found as Strong Biofilm Forming (SBF), there wasn’t any SBF strain in K. terrigena species. In addition to this, clinical materials of urine and sperm were found as the most frequent clinical materials for strong biofilm forming K. ornithinolytica and K. oxytoca isolations respectively (63%; 100%) Secondly, all K. ornithinolytica strains isolated from surgical intensive care unit and all K. oxytoca strains isolated from service units of urology were found as SBF. Apart from these, although the amount of biofilm, formed by co-occurence of K. ornithinolytica - K. oxytoca and K. oxytoca - K. terrigena were more than the amount of biofilm formed by themselves separately, biofilm formation amount of co-occurrence of K. ornitholytica - K. terrigena strains was lower than biofilm formation amount of K. ornithinolytica but higher than biofilm formation amount of K. terrigena. Conclusion: The antibiofilm effects of Citrus limonum and Zingiber officinale essential oils could be used against biofilm Klebsiella aquired infections.